The Effect Of Disclosure Patterns Of Risk Factors In Prospectus On The Relation Between Strategic Alliances And Underpricing Of Biotechnology IPOs - Guo, Ying; Wang, Tawei; Seng, Jia-Lang; Hung, San-Shuan (Journal of Applied Business Research, 2017)
This study observes a significantly negative moderating effect of the disclosing patterns of risk factors in initial public offerings (IPOs) prospectus on the association between strategic alliances and underpricing of biotechnology IPOs. Our findings suggest that strategic alliances mitigate information uncertainties when risk factor disclosures are less helpful, which alleviates the underpricing.
Keywords: Risk Factors; Strategic Alliance; IPO Underpricing